2007
DOI: 10.1038/oby.2007.605
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity‐Related Energy Expenditure With the RT3 and TriTrac Accelerometers in Overweight Adults

Abstract: . Physical activity related energy expenditure with the RT3 and TriTrac accelerometers in overweight adults. Obesity. 2007;15:950 -956. Objective: The objective was to evaluate two accelerometers, the RT3 and the TriTrac-R3D for their ability to produce estimates of physical activity-related energy expenditure (PAEE) in overweight/obese adults. Research Methods and Procedures: PAEE estimates from both accelerometers were obtained in two experiments. In Experiment 1, 13 overweight/obese subjects (BMI 34.2 Ϯ 6.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 47 publications
2
57
2
1
Order By: Relevance
“…The main findings of this multicentre study were that the output from all monitors demonstrated a significant relationship with AEE derived from DLW measurements in line with those typically observed in field validation studies [13,[24][25][26][27][28]. The DynaPort MoveMonitor and the Actigraph GT3X best explained the activity related energy from TEE not related to TBW.…”
Section: Discussionsupporting
confidence: 61%
“…The main findings of this multicentre study were that the output from all monitors demonstrated a significant relationship with AEE derived from DLW measurements in line with those typically observed in field validation studies [13,[24][25][26][27][28]. The DynaPort MoveMonitor and the Actigraph GT3X best explained the activity related energy from TEE not related to TBW.…”
Section: Discussionsupporting
confidence: 61%
“…However, their output is highly variable and difficult to put into clinical context. Interpretation depends on calibration equations and cutoff points for defining light, moderate, vigorous, and total activity [10][11][12][13][14][15]. To date, these cutoff points have been defined for nondisabled, young adults in the supervised setting with correlations to maximum oxygen consumption on cardiopulmonary exercise tests, not during free-living conditions in the population being studied.…”
Section: Introductionmentioning
confidence: 99%
“…The RT3 triaxial accelerometer (StayHealthy, Inc; Monrovia, California) is a waist-mounted device used to measure free-living activity within a range of populations [11][12][13]. Validation and reliability of the RT3 accelerometer for free-living research has been assessed under a number of laboratory-based conditions, including walking and running at standardized speeds on a treadmill [11,[14][15][16][17], using a shaker table [18][19], assessing various mobility tasks [3], and performing structured activities [20].…”
Section: Introductionmentioning
confidence: 99%